Interaction of Bioactive Component of Aframomum melegueta on Molecular Docking - Umoh Esther Udo; Dibua Redeemed Ihimoya; Buraimoh Bose Olaide (International Journal of Biochemistry and Biomolecule Research, 2024)
Computational mimicry of the structure of large complexes created by di- and poly-interaction of molecules has been termed molecular docking. The purpose of molecular docking is the prediction of the three-dimensional structures of interest, this is due to that docking only produces plausible candidate structures. The docking was carried out between the bioactive compounds against 5α-reductase, 3β-hydroxy-steroid dehydrogenase, and 17β-hydroxy-steroid dehydrogenase of returned binding energy, BE (kcal/mol) between -5.9 and -9.0 kcal/mol; -6.0 and -9.4 kcal/mol; and -5.2 kcal/mol and -8.0 kcal/mol respectively. Apigenin and ellagic acid were the compounds with the least binding energy, which translates to high binding affinity to three protein targets. This might be one of the mechanisms in which Aframomum melegueta plays its anti-cancer role in the disease by binding the compounds identified in it to the active site of 5α-reductase, 3β-hydroxy-steroid dehydrogenase, and 17β-hydroxy-steroid dehydrogenase enzymes. Aframomum melegueta has bioactive chemicals that may inhibit three important enzymes involved in human steroid metabolism: 5α-reductase, 3β-hydroxy-steroid dehydrogenase, and 17β-hydroxy-steroid dehydrogenase. This study looked into the potential of these compounds to inhibit these enzymes. The findings of molecular docking tests showed that the binding energies for the different targets ranged from -5.9 to -9.0 kcal/mol, -6.0 to -9.4 kcal/mol, and -5.2 to -8.0 kcal/mol. Interestingly, the lowest binding energies were found for apigenin and ellagic acid, indicating a high binding affinity to all three protein targets. The involvement of hydrogen bonds and hydrophobic interactions between the bioactive chemicals and amino acid residues at the enzyme-binding sites was demonstrated by molecular interaction analysis. These results shed light on the possible mechanism by which chemicals from Aframomum melegueta may impede these enzymes that metabolize steroids to produce anti-cancer effects.
Keywords: Aframomum melegueta; bioactive component; molecular docking; protein-ligand interaction